The effectiveness of cognitive behavioural therapy and third‐wave cognitive behavioural interventions on diabetes‐related distress: A systematic review and meta‐analysis. Issue 11 (16th September 2022) - Jenkinson, Emma; Knoop, Iris; Hudson, Joanna L.; Moss‐Morris, Rona; Hackett, Ruth A.
Abstract: Aim: Diabetes‐related distress is common in diabetes and has implications for well‐being. Cognitive behavioural therapy (CBT) and third‐wave CBT hold promise as treatments for diabetes‐related distress, although previous findings are inconclusive. We aimed to conduct a systematic review with meta‐analysis to understand the efficacy of these interventions in treating diabetes‐related distress, while also assessing the associative benefits of these interventions on depression, anxiety and glycaemic control. We also aimed to conduct a narrative synthesis, and subgroup analyses to identify intervention components most useful in treating diabetes‐related distress. Method: We searched seven electronic databases from inception to April 2021. Data extraction was independently performed by two reviewers. Methodological quality was assessed. The protocol was registered with the Prospective Register Of Systematic Reviews (PROSPERO): CRD42021240628. Results: We included 22 randomised controlled trials investigating the efficacy of CBT and third‐wave CBT interventions on diabetes‐related distress. CBT for diabetes‐related distress significantly reduced distress (SMD = −0.278, p  = 0.010) and depression (SMD = −0.604, p  = 0.016). Third‐wave CBT for diabetes‐related distress significantly reduced anxiety (SMD = −0.451, p  = 0.034). No significant effect of either intervention on glycated haemoglobin was observed. CBT interventions that included a digital component, were delivered by a psychological practitioner, and included behavioural activation bolstered the effects on diabetes‐related distress. Conclusions: CBT aiming to target diabetes‐related distress is beneficial for distress and depression. Third‐wave CBT for diabetes‐related distress is beneficial for anxiety. More work is needed to optimise interventions to improve both mental and physical health outcomes in people with diabetes.